Desenvolvimento de bioprocesso para produção de biocombustíveis obtidos a partir da pirólise rápida de microalgas - Dalmas Neto, Carlos José (2012)
The present work aims to produce and analyze the oil extracted from microalgae and biofuels derived from fast pyrolysis process of your meal. The microalgae are grown in vinasse, a residue of high industrial pollution load and environmental impact of ethanol on national television Although the methods of obtaining the oils produced by microalgae are protected by patents in the field of Ourofino Participações LTD, under numbers WO2008083453-A1, BR200705520-A and-BR200706144 A, the specific conditions for cultivation of microalgae that produce oil, not will be mentioned in details.